Paying For Your Crime: The Pay-to-Stay Jail Program in California - Schultz, Carla Sue (2015)
Many California cities have recently implemented pay-to-stay jail programs at the local level. Pay-to-stay programs provide a safe and private incarceration experience for those who can afford the nightly fee. This study provides a theoretical analysis of the pay-to-stay jail program in relation to mass incarceration and the ever-expanding prison economy. It examines pay-to-stay programs as a new method of stratified punishment, reproducing race and class oppression within the U.S. penal regime. A case study of the Fremont pay-to-stay program offers insight into the implementation, operation, and application process for inmates seeking segregation from general county jail populations. This study concludes that pay-to-stay creates a two-tiered jail system—separating the deserving from the undeserving—and promotes disproportionate treatment within the criminal justice system